Final Report On Control Of Rhinoceros Beetle (Oryctes Rhinoceros) In A Zero Burning Replanted Oil Plam Area Felda Plantation. - Ahmad, Prof. Dr. Abu Hassan (USM, 2006)
The research was carried in FELDA Plantations in LEPAR UTARA 5, 9 and 14 under FELDA Plantation Sdn. Bhd. Central Pahang between September 2003 and January 2006. This is the first kind of research on replanted oil palms (0-4 years old) on the effect of zero burning on the bionomics of rhinoceros beetles (0. rhinoceros) (RB) and its attack on the young palm. The decomposing felled trunks provided ample breeding sites for RB immatures.